SISTEM PEMASARAN JERUK SIAM GUNUANG OMEH DENGAN PENDEKATAN STRUCTURE, CONDUCT, PERFORMANCE (SCP) DI KABUPATEN LIMA PULUH KOTA - Rahma Dini; Mega Amelia Putri; John Nefri (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
The Gunuang Ameh Siam orange (JESIGO) marketing system has complex problems, both in terms of price and non-price. The condition of the relatively high price of oranges (69.23%) compared to other types of oranges has resulted in uncompetitive orange market conditions. On the other hand, farmers as producers are not able to determine the selling price, the role of other marketing institutions is relatively more dominant. This study aims to analyze the marketing of JESIGO with a Structure, Conduct and Performance (SCP) approach. The research was carried out in Kenagarian Koto Tinggi during August 2019 to January 2020. The data used were primary and secondary data. Farmers were selected through purposive sampling (n=20) and snowball sampling for traders (n=11). The data were processed using qualitative and quantitative descriptive analysis. Based on the analysis of market structure, JESIGO marketing tends to lead to an oligopsony market structure. Judging from market behavior, there are 4 marketing channels and marketing functions performed by marketing institutions, namely the exchange function, physical function and facility function. Meanwhile, market performance analysis shows that the share of prices received by farmers (farmer's share) is quite high (>40%). The largest marketing margin is enjoyed by retailers in channel 3. The results of the analysis of the structure, behavior and market performance of the JESIGO orange illustrate that the market is in an efficient condition.